Śāstradīpikā - Pārthasārathimiśra, 11th cent (Caukhambā-Saṃskr̥ta-granthamālā, 1913)
Classical commentary, with supercommentaries, on Jaimini's Mīmāṃsāsūtra, basic work of the Mīmāṃsā school in Hindu philosophy; includes text.